Experimental strategies to increase ammonia yield in plasma catalysis over LTA and BEA zeolites. (21st July 2020) - Gorky, Fnu; Carreon, Moises A; Carreon, Maria L
Abstract: Herein we demonstrate the synthesis of ammonia via atmospheric DBD plasma discharge over LTA and BEA zeolites. The presence of the zeolite in the DBD reactor promoted the ammonia formation at low temperature. The zeolites dielectric constant and pore size greatly influenced the ammonia yields. Ammonia yields of 5.31% for zeolite beta and 5.22% for zeolite 5A were observed, which are at least 4 times higher than the yield obtained in the absence of the zeolites.